2018
DOI: 10.1155/2018/6895146
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Systemic Autoimmunity in Thyroid Disease Subjects

Abstract: Introduction. Individuals with one autoimmune disease are at risk of developing a second autoimmune disease, but the pathogenesis or the sequential occurrence of multiple autoimmune diseases has not been established yet. In this study, we explored the association and sequential occurrence of antibodies in thyroid disease and systemic autoimmune disease subjects. We evaluated thyroid hormones, thyroid-stimulating hormone (TSH), free thyroxine (FT4), thyroid autoantibodies, anti-thyroperoxidase (anti-TPO), and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 22 publications
(24 reference statements)
2
10
1
Order By: Relevance
“…Anti-TPO antibodies were found in 33 individuals (75%) and anti-TG anti-thyroglobulin antibodies were found in 32 patients (72.72%), according to the research. These percentages were similar to those found in Indian research, which found a high percentage of peroxidase antibodies in thyroid gland patients, as well as the greatest percentage of IgM antibodies in 35 autoimmune thyroid patients [19].…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Anti-TPO antibodies were found in 33 individuals (75%) and anti-TG anti-thyroglobulin antibodies were found in 32 patients (72.72%), according to the research. These percentages were similar to those found in Indian research, which found a high percentage of peroxidase antibodies in thyroid gland patients, as well as the greatest percentage of IgM antibodies in 35 autoimmune thyroid patients [19].…”
Section: Resultssupporting
confidence: 90%
“…This supports the theory that infection has a role in the disruption of thyroid gland activities in those who have autoimmune thyroid disease. Thyroid hormones T3, T4, and TSH can be used to distinguish between hypothyroidism and hyperthyroidism, according to studies conducted in India [19,21].…”
Section: Resultsmentioning
confidence: 99%
“…Nisihara R. et al [ 7 ] reported a prevalence of ~ 20% in 70 patients with autoimmune thyroiditis and 84 with GD. Siriwsrdhane et al found a ~ 20% prevalence of ANAs in patients with positive tests for anti-thyroid autoantibodies [ 24 ]. Paul et al found an impressive ~ 80% ANA prevalence in patients with autoimmune thyroiditis [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite reasons concerning disease-related cognition and self-perception discussed above, autoimmunity itself may be the cause for impaired HRQoL and behavioral problems in HT in adults. Autoimmunity in HT may not only affect the thyroid gland but also act systemically ( 64 ) and thereby target the brain as summarized by Leyhe and Müssig ( 65 ). It has been shown that TPO-ABs bind to cerebellar astrocytes ( 66 ), a mechanism by which a direct effect of TPO-ABs on the brain is feasible.…”
Section: Discussionmentioning
confidence: 99%